Perolehan Hak Guna Bangunan (HGB) Bersumber Dari Tanah Hak Milik Oleh PT. Harfhavi Mega Utama (Studi Di Kantor Notaris/PPAT Suhardi, SH, M.Kn) - Yeven dri (Fakultas Hukum Universitas Tamansiswa Padang, 2026)
Land issues are a crucial factor influencing development. Land issues arise not from a lack of adequate legislation, nor from a lack of human capacity to implement them, but rather from a lack of understanding and appreciation of the agrarian or land sector. Article 4 of Law Number 5 of 1960 concerning Basic Agrarian Principles states that: